Comparison of 3- and 90-day bond strengths of 3 types of cement to nickel-chromium alloy - de Sousa Ervolino, Isabela Caroline [UNESP]; Bento, Victor Augusto Alves [UNESP]; Brunetto, Juliana Lujan [UNESP]; de Melo Laborde, Brenda Farias Cavalcanti Vaz; Arantes, Isabela Samudio; Castillo, Daisilene Baena (My University, 2022)
The purpose of this in vitro study was to compare the 3- and 90-day bond strengths of 3 cements used for luting metal-ceramic crowns. Zinc phosphate cement (ZPC; SS White), resin-modified glass ionomer cement (RMGIC; Fuji Plus), and self-adhesive resin cement (SARC; RelyX U200) were assessed in 2 different treatment conditions (with and without microsandblasting of the alloy) and at 2 experimental times (3 days [E1] and 90 days [E2] after cementation). The buccal surfaces of 84 bovine teeth were ground until the dentin was exposed, and 84 nickel-chromium alloy plates cast from a resin model were cemented to the dentin surfaces with 1 of the 3 cements (n = 28). In half of the specimens of each group (n = 14), the bonding surfaces of the nickel-chromium plates received 6 seconds of microsandblasting with 45-μm aluminum oxide particles prior to cementation. The compressive shear bond strengths of the specimens were evaluated in a universal testing machine at E1 and E2 (n = 7). The SARC group showed the greatest bond strength, followed by the RMGIC group, while the bond strength of the ZPC group was significantly lower (P < 0.01). For the RMGIC specimens subjected to microsandblasting, there was a statistically significant difference between the mean bond strengths at E1 and E2 (P = 0.040). All of the other cement and treatment groups showed statistically similar adhesion results at E1 and E2 (P > 0.05). The complementary test by Šidák revealed that the cements Fuji Plus and RelyX U200 showed higher values at E2 and were statistically similar to each other (P > 0.05). Although RMGIC specimens showed a lower initial bond strength than SARC specimens, the fact that the microsandblasted RMGIC subgroup was the only one that demonstrated a significant increase in bond strength with aging suggests that RMGIC can be a material of first choice because it also costs less than SARC.
Keywords: dental crowns; metal-ceramic alloys; resin-modified glass ionomer cement; self-adhesive resin cement; zinc phosphate cement